Optimal array arrangement of oscillating wave surge converters: an analysis based on three devices - Benites-Munoz, Daniela; Huang, Luofeng; Thomas, Giles (Elsevier, 2024)
Wave farms consist of arrays of wave energy converters. However, ocean waves perturbed by one device will interact with its neighbouring devices, which can lead to more or less power yielded than operating the devices in isolation. Therefore, it is of significant interest to study the optimal layout and spacing to deploy multiple devices. In this work, a validated high-fidelity computational approach is used to study the optimal arrays of three oscillating wave surge converters by systematically varying the array arrangement in different wave conditions. The simulations demonstrate the wave interaction with multiple dynamic bodies and how this affects the overall power output. Furthermore, novel empirical rules are derived to design the optimal constructive layout for three devices in a given wave condition, and this can be extended to cases of numerous devices.
Keywords: Wave farm; Oscillating wave surge converter; Array arrangement; Computational fluid dynamics; Reactive power take-off; OpenFOAM